Atypical histiocytosis in the lung - Li, Hong; Cao, Weijun; Li, Huiping; Zhang, Rongxuan; Zhou, Ying; Xu, Jinfu; Garfield, David H. (Journal of Thoracic Disease, 2013)
Objective: To report a rare case of atypical histiocytic tumor of the lung with a review of literature. Methods: The clinical materials were noted. Literature related to this condition from the past 50 years was reviewed from the group of histiocytic tumors. Results and conclusions: Clinical manifestations were non-specific. The imaging characteristics of our case were infiltrative lesions with multiple cysts in both lungs. Pathology showed nodular proliferation of atypical cells. Immunohistochemistry suggested a histiocytic origin of the infiltrating atypical cells. Because the pathological findings did not fall into any particular category of typical histiocytic tumors, the final diagnosis was atypical histiocytic tumor. The presentation of atypical histiocytic tumor of the lungs, only, with infiltrative lesions and multiple air cysts seems very rare, with pathological examination being “gold standard” for the diagnosis.